In vitro antibacterial activity of an oxygen-based mouthwash compared to chlorhexidine digluconate against Fusobacterium nucleatum (Research, Society and Development, 2026)
Objective: To compare the in vitro antibacterial activity of chlorhexidine digluconate mouthwash and an oxygen-based mouthwash against Fusobacterium nucleatum. Materials and Methods: The antibacterial effect was evaluated using the agar diffusion microbiological assay with the following mouthwashes: blue®m oxygen mouthwash at 100% (B1), blue®m oxygen mouthwash at 75% (B2), blue®m oxygen mouthwash at 50% (B3), and a 0.12% chlorhexidine digluconate solution from Perio-AID at 100% (C1), tested against Fusobacterium nucleatum ATCC 25586 strains. Results: The findings showed that blue®m at concentrations of 100% and 75% exhibited antibacterial activity comparable to chlorhexidine. However, blue®m at a concentration of 50% demonstrated a smaller inhibition zone compared with chlorhexidine (p = 0.024). Conclusions: Higher concentrations of blue®m produced an inhibitory halo against Fusobacterium nucleatum similar to that observed with chlorhexidine digluconate, whereas lower concentrations resulted in reduced antibacterial inhibition when compared with chlorhexidine.